Desenvolvimento de um modelo fuzzy para determinação do calor latente com aplicação em sistemas de irrigação - Souza, Orlando Tadeu Lima de [UNESP] (2004)
The determination of the necessary amount of water is one of the main parameters of an agriculture irrigation system. One of the efficient consequences of the measurements of the system is the increase of productivity, and therefore the profitable advantage of it. The satisfactory amount of water is therefore a very important condition for the growing accomplishment of the plant causing the production, with fewer costs. The aim of this work is the development of a mathematical model, based on the Fuzzy Theory, to determine the stream of latent heat, having as a result the calculation of the transpiration dissipated that defines the necessary amount of water for the cultivations of plants in protected environments; intending above all the balance of water usage and electricity in the agriculture activity. This model can be used in the implementation of a system that controls the outflowing of irrigations, determining the time and volume of water that is necessary for the furnishing of it. The required amount of water for the supplement of the system is the gathered through the determination of the stream of latent heat, for its highness is the equivalent to the volume of water transpired by the plant. The model adopts three variables to begin with, which are: the balance of solar radiation, stream of the soil heat and the air temperature, which are the amounts that are measured by the installed equipments in the planted area. Through this model is possible to determine the stream of latent heat (LE), having it as the variable of exit of the model. To have this model validated there were used data, that were obtained in the experiment that was done by the cultivation of Euruca Sativa L., in an incubator covered by polyethylene at the Department of Science, at Faculdade de Ciências Agrônomicas and the results were obtained trough simulations that were done in the Laboratory of this Institution...